The Role and Contribution of Private Sector towards the Realisation of Kenya’s Vision 2030. - Kilimo, Timothy (2012)
The private sector has increasingly been viewed as the engine for growth and development. The primary purpose of this study is to provide a better understanding of what role the private sector plays in development and in particular, it seeks to examine whether the impact of private sector Corporate Social Responsibility (CSR) initiatives and interventions can contribute towards the realisation of Kenya’s Vision 2030. To do so, the study analysed the web contents of fourteen selected companies operating in Kenya to examine their motivation to undertake CSR and how their CSR initiatives and interventions contributed to the attainment of the three pillars of Vision 2030 that is the economic, social and political pillars.